Cytohistological and immunohistochemical features of a mammary invasive pleomorphic lobular carcinoma in a dog - Salgado, Breno S. [UNESP]; Monteiro, Lidianne N. [UNESP]; Colodel, Márcia M. [UNESP]; Figueiroa, Fernanda C. [UNESP]; Nonogaki, Suely; Rocha, Rafael M.; Rocha, Noeme Sousa [UNESP] (Springer Nature, 2012)
This case report describes a case of a mammary invasive pleomorphic lobular carcinoma in a female dog. Cytology revealed small cohesive clusters of cells and many scattered single large round cells with eccentric nuclei. Histologically, the neoplasm presented plasmacytoid cells with multiple, often bizarre nuclei and an invasive pattern with cells occasionally arranged in Indian files. Vascular invasion was consistently present. Tumour cells also revealed loss of E-cadherin immunoexpression and positive immunoreactivity for HER2/c-erbB2, oestrogen receptor alpha, cytokeratin 19, and Ki67 (52 %), and the tumour was characterised as a mammary invasive pleomorphic lobular carcinoma. This is an interesting case since this is a rare condition that is not widely recognised in dogs. © 2012 Springer-Verlag London Limited.
Keywords: c-ErbB2; Cytodiagnosis; Cytokeratin 19; E-cadherin; Mammary lobular carcinoma; Mammary neoplasms; Oestrogen receptor alpha